2020
DOI: 10.1101/2020.03.11.987180
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Super-enhancer switching drives a burst in germline gene expression at the mitosis-to-meiosis transition

Abstract: 26The testis has the most diverse and complex transcriptome of all organs due to bursts in 27 expression of thousands of germline-specific genes. Much of this unique gene expression takes 28 place when mitotic germ cells differentiate and enter into meiotic prophase. Here, we 29 demonstrate that the genome-wide reorganization of super-enhancers (SEs) drives bursts of 30 germline genes after the mitosis-to-meiosis transition. At the mitosis-to-meiosis transition, 31 mitotic SEs dissolve while meiotic SEs are es… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 71 publications
0
3
1
Order By: Relevance
“…SMARCC1 promotes XCI by increasing promoter accessibility of the inactive X chromosome (Xi). Interestingly, during MSCI, sex-linked chromatin displays enhanced accessibility (Maezawa et al, 2018b). In contrast, our studies showed that BAF-A limits rather than enhances sex-linked chromatin accessibility.…”
Section: Discussioncontrasting
confidence: 75%
“…SMARCC1 promotes XCI by increasing promoter accessibility of the inactive X chromosome (Xi). Interestingly, during MSCI, sex-linked chromatin displays enhanced accessibility (Maezawa et al, 2018b). In contrast, our studies showed that BAF-A limits rather than enhances sex-linked chromatin accessibility.…”
Section: Discussioncontrasting
confidence: 75%
“…Therefore, we postulate that retrotransposition of ERVs provides new binding sites for key transcription factors, which, in turn, function as newly evolved cis regulatory elements for many genes. Importantly, we have also shown that A-MYB is associated with super-enhancers to drive the expression of key germline genes (Maezawa et al) 30 . Therefore, an A-MYB-dependent mechanism appears to lie at the heart of two distinct enhancer types: (1) super-enhancers, which drive robust activation of germline genes; and (2) ERV-driven, rapidly evolving enhancers, which fine-tune the expression of species-specific germline genes.…”
Section: Discussionmentioning
confidence: 87%
“…Given that ERVs are interspersed throughout the genome, we hypothesized that ERVs function as enhancers that drive the expression of spermatogenesis-specific genes. To test this hypothesis, we analyzed the ChIP-seq (chromatin immunoprecipitation sequencing) signal enrichment for H3K27 acetylation (H3K27ac), a marker of active enhancers, in PS 29 (Maezawa et al) 30 . Through the thresholding of H3K27ac enrichment and accessible chromatin at individual ERV loci (see Methods ), we defined a category of ERVs said to be “enhancer-like” in PS (ERV1: 116 enhancer-like loci; ERVK: 970 enhancer-like loci; ERVL: 36 enhancer-like loci; Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation